2016
DOI: 10.1039/c5fd00187k
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of large surface area lanthanum based perovskite supports for AuPt nanoparticles: tuning the glycerol oxidation reaction pathway by switching the perovskite B site

Abstract: Gold and gold alloys, in the form of supported nanoparticles, have been shown over the last three decades to be highly effective oxidation catalysts. Mixed metal oxide perovskites, with their high structural tolerance, are ideal for investigating how changes in the chemical composition of supports affect the catalysts' properties, while retaining similar surface areas, morphologies and metal co-ordinations. However, a significant disadvantage of using perovskites as supports is their high crystallinity and sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…The materials prepared with and without PVA were employed for selective aqueous phase glycerol oxidation to investigate the effect of the polymer stabiliser on the catalytic performance. The general reaction pathway is illustrated in Scheme , which is based on the observations obtained in this study and of reaction pathways reported in the literature . The first oxidative dehydrogenation step forms glyceraldehyde or dihydroxyacetone, which are in equilibrium.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The materials prepared with and without PVA were employed for selective aqueous phase glycerol oxidation to investigate the effect of the polymer stabiliser on the catalytic performance. The general reaction pathway is illustrated in Scheme , which is based on the observations obtained in this study and of reaction pathways reported in the literature . The first oxidative dehydrogenation step forms glyceraldehyde or dihydroxyacetone, which are in equilibrium.…”
Section: Resultsmentioning
confidence: 84%
“…This is notable, since TEM characterization indicated that the preparation without capping agent resulted in larger, ill‐shaped Au NPs (Figure and Supporting Information). It is generally described in the literature that smaller Au NPs show an improved catalytic activity for glycerol oxidation . Hence, this observation might imply that, besides the detrimental effect on the particle morphology, the absence of PVA can have a positive impact on the catalytic performance.…”
Section: Resultsmentioning
confidence: 85%
“…In general, the acidity of catalysts corresponded to the unsaturated M cations (Ce, La, and Co) exposed on the surface [37]. Entry of La and Co cations (La 3+ and Co 3+ ) in the structure of ternary catalyst affects the acidic sites.…”
Section: B the Characterization Of Ternary Ce/la/co Catalystsmentioning
confidence: 99%
“…Thus, we cannot support this proposed reaction pathway as the sole reason for glycolic acid formation. Glycolic acid is rather formed by C−C cleavage of glyceric acid or directly as primary product. The direct formation of glycolic acid through glyceraldehyde or dihydroxyacetone intermediates was reported by Ketchie et al.…”
Section: Catalytic Glycerol Oxidation Experimentsmentioning
confidence: 99%